Characteristics of productivity of soft winter wheat samples from Common Bunt-Resistant Nursery (CBUNT-RES) in the southern Forest-Steppe zone of Ukraine - С. М. Холод; В. М. Кір’ян; Р. С. Вискуб (Plant Varieties Studying and Protection)
Purpose. Evaluate the introduced samples of soft winter wheat from the international nursery Common Bunt-Resistant Nursery (CBUNT-RES) of different ecological and geographical origin in the southern part of the Forest-Steppe zone of Ukraine according to a set of productivity indicators in order to define the most valuable samples and describe them.